1203. Systemic, Mucosal Immune Activation And Psycho-sexual Health in HIV-Infected And Uninfected Women: Evaluation of Biomarkers And Environmental Stimuli. (31st December 2020) - Nijhawan, Parni; Nijhawan, Parni; Carraro, Anna; Marocco, raffaella; Vita, Serena; Kertusha, Blerta; Mascia, Claudia; Lichtner, Miriam; Mastroianni, Claudio; Zingaropoli, Maria Antonella; Masci, Georgio; Ianiri, Palmieri; et al.
Abstract: Background: HIV infection in women in disproportionate ratios as compared to men has been a grave concern over the years. It is in proportion to reproductive and hormonal differences making women more vulnerable. It elicits an Immune response which can be monitored by analysing various factors such as mucosal immunity, sexual behaviour, biomarkers in the plasma, serum and vaginal lavage and vaginal infections. Aim: Evaluating and comparing the systemic and mucosal immuno-inflammatory status, the female sexual function (FSF) and generalized anxiety in HIV+ women on successful HAART with healthy women (HW). Methods: We enrolled 53 subjects (23 HIV+ women on successful HAART and 30 Healthy women (HW)) with no statistical differences in age. The figure (named: methodology) below explains the methods applied: Cytometry and Kit ELISA were used to estimate lymphocytes and all cytokines. Women were also tested for co-morbidities such as diabetes, blood pressure, HCV, cervical cancer etc. Statistical analysis was performed using PRISM 8.0. Methodology Results: Higher CD4 and CD8 cell count was observed in HW compared to HIV+ women (p=0.02, p=0.004).Plasma levels of sCD 163, CXCL-10, IL-1, IL-6 and IL-8 were significantly higher in HIV women as compared to HW(p< 0.001), while IL-6 and IL8 were lower in the VL of HIV women. An ASCUS in HW was found for PAP Test. CXCL-10 was correlated to estradiol levels (r=0.8, p=0.02). 57% reported FSD and 43% had a FSFI score≤10. A significant difference between the two groups in the FSFI score (p=0.007) was found, particularly in sexual desire, arousal and pain. A positive correlation between level of testosterone and FSFI score was found only in HIV+ women (p=0.02; r= 0.74). 17% of women presented an anxiety disorder. Z-index was associated with orgasm domains (p=0.01; r=-0.4) and CD4+ T cells (p=0.02; r=-0.45). Conclusion: Higher plasma levels of the cytokines despite successful antiretroviral therapy were observed. At the mucosal level evaluating the balance within pro anti-inflammatory cytokines and micro-biome will be interesting to study. FSD is detected in more than half of HIV infected women and seems to be related to testosterone levels. The comparison with uninfected women underlying a persistent gap in quality of life of young HIV women should be bridged. Disclosures: All Authors : No reported disclosures